Characterization of Pathogenesis and Inflammatory Responses to Experimental Parechovirus Encephalitis - Jan, Ming-Wei; Su, Hong-Lin; Chang, Tsung-Hsien; Tsai, Kuen-Jer (Frontiers in Immunology, 2021)
Human parechovirus type 3 (PeV-A3) infection has been recognized as an emerging etiologic factor causing severe nerve disease or sepsis in infants and young children. But the neuropathogenic mechanisms of PeV-A3 remain unknown. To understand the pathogenesis of PeV-A3 infection in the neuronal system, PeV-A3-mediated cytopathic effects were analyzed in human glioblastoma cells and neuroblastoma cells. PeV-A3 induced interferons and inflammatory cytokine expression in these neuronal cells. The pronounced cytopathic effects accompanied with activation of death signaling pathways of apoptosis, autophagy, and pyroptosis were detected. A new experimental disease model of parechovirus encephalitis was established. In the disease model, intracranial inoculation with PeV-A3 in C57BL/6 neonatal mice showed body weight loss, hindlimb paralysis, and approximately 20% mortality. PeV-A3 infection in the hippocampus and cortex regions of the neonatal mouse brain was revealed. Mechanistic assay supported the in vitro results, indicating detection of PeV-A3 replication, inflammatory cytokine expression, and death signaling transduction in mouse brain tissues. These in vitro and in vivo studies revealed that the activation of death signaling and inflammation responses is involved in PeV-A3-mediated neurological disorders. The present results might account for some of the PeV-A3-associated clinical manifestations.